I was trying to solve the integral $\int_0 ^{\frac{\pi}{4}} \sqrt{\tan{x}}dx$ and I noticed I can do the following:

$$\int_0 ^{\frac{\pi}{4}} \sqrt{\tan{x}}dx=\int_0 ^{\frac{\pi}{4}} \sqrt{\tan{x}} \sec^2(x) -\int_0 ^{\frac{\pi}{4}} \sqrt{\tan{x}} \tan^2(x) dx $$ $$=\int_0 ^{\frac{\pi}{4}} \sqrt{\tan{x}} \sec^2(x) -\int_0 ^{\frac{\pi}{4}} \tan^{2+\frac{1}{2}}(x) \sec^2(x)dx + \int_0 ^{\frac{\pi}{4}} \tan^{4+\frac{1}{2}}(x) $$ continue with that and we will get $$\int_0 ^{\frac{\pi}{4}} \sqrt{\tan{x}}dx=\sum_{k=0}^n \left(\int_0 ^{\frac{\pi}{4}} \tan^{2k+\frac{1}{2}}(x) \sec^2(x)dx \right) + (-1)^{n+1}\int_0 ^{\frac{\pi}{4}} \tan^{2n+2+\frac{1}{2}}(x) dx$$ since for any converging positive sequence $a_n$ $(\sum a_k)^n >\sum (a_k ^n)$ $\int_0 ^{\frac{\pi}{4}} \tan^{n}(x) dx <\left( \int_0 ^{\frac{\pi}{4}} \tan(x) dx \right) ^n \to 0$ so we get $$ \int_0 ^{\frac{\pi}{4}} \sqrt{\tan{x}}dx=2 \ \lim_{n \to \infty } \sum_{k=0} ^ n \frac{(-1)^k}{4k+3}=\frac{\pi +\ln{(3-2 \sqrt{2})}}{2 \sqrt{2}} $$

I don't know if my approach is correct or not but even if it is correct I am interested in finding out if there are any other more obvious ways to evaluate $ \sum\limits_{k=0} ^{\infty} \frac{(-1)^k}{4k+3}$ as my approach is very difficult to notice if try to solve $ \sum\limits_{k=0} ^{\infty} \frac{(-1)^k}{4k+3}$ without any mention of the integral.

another question can we generalise this result for all $m \in \mathbb{R}$ st $m>1$ $$ \int_0 ^{\frac{\pi}{4}} \left(\tan{x} \right)^{\frac{1}{m}} dx=m \ \sum_{k=0} ^ {\infty } \frac{(-1)^k}{2mk+m+1} $$

  • 5
    $\begingroup$ Is there a reason you are writing $\lim_{n \to \infty } \sum_{k=0} ^ n \frac{(-1)^k}{4k+3}$ instead of the usual easier notation $\sum_{k=0} ^ \infty \frac{(-1)^k}{4k+3}$? $\endgroup$
    – jjagmath
    Oct 29, 2023 at 19:56
  • $\begingroup$ Your argument to prove that $\displaystyle \lim_{n\rightarrow \infty}\int_0 ^{\frac{\pi}{4}} \tan^{n}(x) dx=0$ is not good but this limit is, indeed, $0$. $\endgroup$
    – FDP
    Oct 31, 2023 at 2:59
  • $\begingroup$ @FDP I noticed that it is not complete and I don't know how to fix it maybe you can help me with that $\endgroup$
    – pie
    Oct 31, 2023 at 3:01
  • 1
    $\begingroup$ If $\displaystyle J_n=\int_0 ^{\frac{\pi}{4}} \tan^{n}(x) dx$, to prove that $\displaystyle \lim_{n\rightarrow \infty}J_n=0$, perform the change of variable $u=\tan x$, you get $\displaystyle J_n=\int_0^1 \frac{x^n}{1+x^2}dx$. Now, the integrand is bound by $x^n$ so $\displaystyle 0\leq J_n\leq \int_0^1 x^ndx$ the latter integral is $\dfrac{1}{n+1}$ $\endgroup$
    – FDP
    Oct 31, 2023 at 3:08
  • $\begingroup$ @FDP thank you very much $\endgroup$
    – pie
    Oct 31, 2023 at 5:28

3 Answers 3


One way is to use the power series trick: For $1\leq m<n$, we have

\begin{align} S(m,n)&:=\sum_{k=0}^\infty\frac{(-1)^k}{nk+m}\\[.4em] &=\sum_{k=0}^\infty\int_0^1(-1)^kx^{nk+m-1}dx\\[.4em] &=\int_0^1x^{m-1}\sum_{k=0}^\infty(-x^n)^kdx\\[.4em] &=\int_0^1\frac{x^{m-1}}{x^n+1}dx. \end{align}

Now for your generalisation, taking $(m,n)=(m+1,2m)$ leads to

$$S(m+1,2m)=\int_0^1\frac{x^m}{x^{2m}+1}dx=\frac1m\int_0^{\pi/4}(\tan u)^\frac1mdu$$

where the second step is by the substitution $x=(\tan u)^\frac1m$.

If $1\leq m<n$ are integers, we can evaluate the integral using digamma function $\psi$, that is,

\begin{align} S(m,n)&=\frac1{2n}\left(\psi\left(\frac{m+n}{2n}\right)-\psi\left(\frac{m}{2n}\right)\right)\\ &=\frac\pi{2n}\csc\left(\frac{m\pi}n\right)+\frac2n\sum_{k=1}^{n-1}\ln\left(\csc\left(\frac{k\pi}{2n}\right)\right)\sin\left(\frac{mk\pi}n+\frac{k\pi}2\right)\sin\left(\frac{k\pi}2\right). \end{align}

For the first equality you can find a proof in this post, and for the second we use Gauss's digamma theorem with a few trig identities.


\begin{gathered} \sum\limits_{k = 0}^\infty {\frac{{{{\left( { - 1} \right)}^k}}}{{4k + 3}} = } \sum\limits_{k = 0}^\infty {{{\left( { - 1} \right)}^k}\int\limits_0^1 {{x^{4k + 2}}dx} = } \int\limits_0^1 {\left( {\sum\limits_{k = 0}^\infty {{{\left( { - 1} \right)}^k}{x^{4k + 2}}} } \right)dx} \hfill \\ = \int\limits_0^1 {\frac{{{x^2}}}{{1 + {x^4}}}dx} = \frac{1}{2}\int\limits_0^1 {\frac{{2{x^2}}}{{1 + {x^4}}}dx} = \frac{1}{2}\int\limits_0^1 {\frac{{{x^2} + 1}}{{1 + {x^4}}}dx} + \frac{1}{2}\int\limits_0^1 {\frac{{{x^2} - 1}}{{1 + {x^4}}}dx} \hfill \\ = \frac{1}{2}\int\limits_0^1 {\frac{{1 + \frac{1}{{{x^2}}}}}{{\frac{1}{{{x^2}}} + {x^2}}}dx} + \frac{1}{2}\int\limits_0^1 {\frac{{1 - \frac{1}{{{x^2}}}}}{{\frac{1}{{{x^2}}} + {x^2}}}dx} = \frac{1}{2}\int\limits_0^1 {\frac{1}{{{{\left( {x - \frac{1}{x}} \right)}^2} + 2}}d\left( {x - \frac{1}{x}} \right)} + \frac{1}{2}\int\limits_0^1 {\frac{1}{{{{\left( {x + \frac{1}{x}} \right)}^2} - 2}}d\left( {x + \frac{1}{x}} \right)} \hfill \\ = \left. {\frac{1}{2}\frac{1}{{\sqrt 2 }}\arctan \left( {\frac{1}{{\sqrt 2 }}\left( {x - \frac{1}{x}} \right)} \right)} \right|_0^1 + \left. {\frac{1}{2}\frac{1}{{2\sqrt 2 }}\ln \left| {\left. {\frac{{\sqrt 2 - x - \frac{1}{x}}}{{\sqrt 2 + x + \frac{1}{x}}}} \right|} \right.} \right|_0^1 \hfill \\ = \frac{1}{2}\frac{1}{{\sqrt 2 }}\frac{\pi }{2} + \frac{1}{2}\frac{1}{{2\sqrt 2 }}\ln \left( {3 - 2\sqrt 2 } \right) = \frac{\pi }{{4\sqrt 2 }} + \frac{1}{{2\sqrt 2 }}\ln \left( {\sqrt 2 - 1} \right) \hfill \\ \end{gathered}


\begin{align}J&=\int_0^{\frac{\pi}{4}}\sqrt{\tan x}dx\\ &\overset{u=\sqrt{\tan x}}=\int_0^1\frac{2u^2}{1+u^4}du\\ &=\int_0^1 \left(2u^2\sum_{n=0}^\infty (-1)^nu^{4n}\right)du\\ &=2\int_0^1 \left(u^2\sum_{n=0}^\infty (-1)^nu^{4n+2}\right)du\\ &=2\sum_{n=0}^\infty(-1)^n\left(\underbrace{\int_0^1 u^{4n+2}du}_{=\frac{1}{4n+3}}\right)\\ &=2\sum_{n=0}^\infty\frac{(-1)^n}{4n+3}\\ \end{align} On the other hand, \begin{align}K&=\int_0^1 \frac{u^2}{1+u^4}du\\&\overset{z=\frac{1}{u}}=\int_1^{\infty}\frac{1}{1+z^4}dz\\ 2K&=\int_0^1 \frac{u^2}{1+u^4}du+\int_0^{\infty}\frac{1}{1+z^2}dz-\int_0^1\frac{1}{1+z^4}dz\\ &=\int_0^1 \frac{u^2-1}{1+u^4}du+\underbrace{\int_0^\infty\frac{1}{1+z^4}dz}_{=L}\\ L&\overset{w=\frac{1}{z}}=\int_0^\infty \frac{w^2}{1+w^4}dw\\ 4K&=2\int_0^1 \frac{u^2-1}{1+u^4}du+\int_0^\infty\frac{1+z^2}{1+z^4}dz\\ &=2\underbrace{\int_0^1 \frac{1-\frac{1}{u^2}}{\left(u+\frac{1}{u}\right)^2-2}du}_{w=u+\frac{1}{u}}+\underbrace{\int_0^\infty\frac{1+\frac{1}{z^2}}{\left(z-\frac{1}{z}\right)^2+2}dz}_{w=z-\frac{1}{z}}\\ &=-2\int_2^\infty\frac{1}{w^2-2}dw+\int_{-\infty}^{+\infty}\frac{1}{w^2+2}dw\\ &=-\frac{1}{\sqrt{2}}\left[\ln\left(\frac{w-\sqrt{2}}{w+\sqrt{2}}\right)\right]_2^{\infty}+\frac{1}{\sqrt{2}}\left[\arctan\left(\frac{w}{\sqrt{2}}\right)\right]_{-\infty}^{+\infty}\\ &\boxed{K=\frac{1}{4\sqrt{2}}\ln\left(\frac{\sqrt{2}-1}{\sqrt{2}+1}\right)+\frac{\pi}{4\sqrt{2}}}\\ \end{align}

Therefore, \begin{align}\boxed{J=\frac{1}{2\sqrt{2}}\ln\left(\frac{\sqrt{2}-1}{\sqrt{2}+1}\right)+\frac{\pi}{2\sqrt{2}}}\\ \boxed{\sum_{n=0}^\infty\frac{(-1)^n}{4n+3}=\frac{1}{4\sqrt{2}}\ln\left(\frac{\sqrt{2}-1}{\sqrt{2}+1}\right)+\frac{\pi}{4\sqrt{2}}} \end{align}

PS: Sorry,i have just observed my solution is the same than the one of OnTheWay.


You must log in to answer this question.

Not the answer you're looking for? Browse other questions tagged .